Perubahan Perilaku Sosial Remaja Mantan Pecandu Alkohol Terhadap Interaksi Sosial - Muhammad Ikhsan Hadi; Ati Kusmawati (Lembaga Pengembangan Kinerja Dosen, 2024)
Juvenile delinquency, including alcohol consumption, is a significant social issue affecting adolescents' social interactions. This study aims to evaluate the differences in social interactions among adolescents before and after ceasing alcohol consumption in Pondok Ranji Village. Data were collected using a qualitative method with purposive sampling techniques, involving observations, interviews, and documentation. Data analysis was performed through data reduction, data presentation, and conclusion drawing. The results indicate that behavioral changes in former alcohol users are closely related to internal and external factors, such as self-awareness and family responses. These changes positively impact social interactions, as evidenced by improved communication quality and more harmonious relationships with family and acquaintances. The findings highlight the importance of motivating factors and social support in the recovery process of adolescents from alcohol consumption.